Answer:
-1
Step-by-step explanation:
-6(-2)= -6*-2= 12
4(-3)= 4*-3= -12
12/-12= -1
I dont think so. and you should add and then reseporate the groups.
The slant height of the pyramid can be calculated using Pythagoras theorem. Therefore, the slant height is 6.7 mm
<h3>How to find slant height of a pyramid?</h3>
The slant height x, can be found using Pythagoras theorem,
Therefore,
c² = a² + b²
where
- c = hypotenuse
- a and b are other two legs.
Therefore,
x² = 4.5² + 5²
x² = 20.25 + 25
x² = 45.25
x = √45.25
x = 6.72681202354
x = 6.7 mm
learn more on pyramid here: brainly.com/question/11805304
#SPJ1
There is a higher chance that the dad is right because he is betting on a pretty much 50/50 chance while the mom is betting on a 25% chance